Enantioselective Transesterification by Candida antarctica Lipase B Immobilized on Fumed Silica - Kramer, Martin; Cruz, Juan C.; Pfromm, Peter H.; Rezac, Mary E.; Czermak, Peter (My University, 2010)
Enzymatic catalysis to produce molecules such as perfumes, flavors, and fragrances has the advantage of allowing the products to be labeled “natural” for marketing in the U.S., in addition to the exquisite selectivity and stereoselectivity of enzymes that can be an advantage over chemical catalysis. Enzymatic catalysis in organic solvents is attractive if solubility issues of reactants or products, or thermodynamic issues (water as a product in esterification) complicate or prevent aqueous enzymatic catalysis. Immobilization of the enzyme on a solid support can address the generally poor solubility of enzymes in most solvents. We have recently reported on a novel immobilization method for Candida antarctica Lipase B on fumed silica to improve the enzymatic activity in hexane. This research is extended here to study the enantioselective transesterification of (RS)-1-phenylethanol with vinyl acetate. The maximum catalytic activity for this preparation exceeded the activity (on an equal enzyme amount basis) of the commercial Novozyme 435® significantly. The steady-state conversion for (R)-1-phenylethanol was about 75% as confirmed via forward and reverse reaction. The catalytic activity steeply increases with increasing nominal surface coverage of the support until a maximum is reached at a nominal surface coverage of 230%. We hypothesize that the physical state of the enzyme molecules at a low surface coverage is dominated in this case by detrimental strong enzyme-substrate interactions. Enzyme-enzyme interactions may stabilize the active form of the enzyme as surface coverage increases while diffusion limitations reduce the apparent catalytic performance again at multi-layer coverage. The temperature-, solvent-, and long-term stability for CALB/fumed silica preparations showed that these preparations can tolerate temperatures up to 70°C, continuous exposure to solvents, and long term storage.
Keywords: Candida antarctica Lipase B; Hexane; Enzyme immobilization; Fumed silica; Enantioselective transesterification; Enzyme stability